Safety and Effectiveness of the Pfizer-BioNTech COVID-19 Vaccine among Health Staff in Sulaimani City, Iraq: A Prospective Cohort Study - Rahim, Bestun Ibrahim Hama; Ali, Seenaa Muhammed (Iraqi Journal of Science, 2024)
A cohort study was conducted among 210 health staff members in Sulaimani city to assess the safety and effectiveness of the Pfizer-BioNTech vaccine. They were divided into two groups: vaccinated and unvaccinated. The vaccinated group received two doses of the Pfizer vaccine, while the unvaccinated group did not receive any vaccines during this study. Vaccine reactogenicity was assessed using a self-report form. Whereas vaccine immunogenicity was assessed by testing the anti-receptor binding domain IgG (anti-RBD IgG) antibody. Several adverse effects were observed with each dose. The most frequent adverse effects were pain at the inoculation site, tiredness, myalgia and fever. The average adverse effects per person in the first and second doses were 5.3 (SD 3.3) and 6.3 (SD 3.5) respectively (p = 0.005). The immunized group’s anti-RBD IgG antibody levels were greatly improved after taking the first and second doses (32.50 and 44.92 binding antibody units (BAU)/mL respectively). After eight months of taking the two doses, the antibody level dropped to 17.00 BAU/mL. This study indicates that the vaccine can be safe and effective for enhancing antibody production.